Corporate Responses to Climate Change and Financial Performance: The Impact of Climate Policy - Andreas Ziegler; Timo Busch; Volker H. Hoffmann (ETH Zurich, CER-ETH - Center of Economic Research, 2009)
This paper examines the relationship between corporate activities to address climate change and stock performance. By separately analyzing the US and European stock markets for different sub-periods, we highlight the impact of the underlying climate policy regime. Methodologically, we compare risk-adjusted returns of stock portfolios comprising corporations that differ in their responses to climate change. In this respect, we apply the flexible Carhart fourfactor model besides the restricted one-factor model based on the Capital Asset Pricing Model (CAPM). While our portfolio analysis shows negative relationships over the entire observation period from 2001 to 2006, we find that a trading strategy, which bought stocks of corporations with a higher level of responses to climate change and sold stocks of corporations with a lower level, led to negative abnormal returns in regions and periods with less ambitious climate policy, but to positive abnormal returns in regions and periods with stringent climate policy.
Keywords: Q54; Q48; M14; G11; G12; 330; Climate change; Climate policy; Corporate environmental performance; Financial performance; Portfolio analysis; Asset pricing models; Klimawandel; Umweltpolitik; Umweltmanagement; Portfolio-Management; CAPM; Schweiz